Mechanisms Underlying Chronic Binge Alcohol Exposure-Induced Uterine Artery Dysfunction in Pregnant Rat - Naik, Vishal D. (Alcohol Clin Exp Res, 2018)
BACKGROUND: A cardinal feature of fetal alcohol syndrome is growth restriction. Maternal uterine artery adaptations to pregnancy correlate with birth weight and survival. We hypothesized that gestational binge alcohol exposure impairs maternal uterine vascular function, affecting endothelial nitric oxide-mediated vasodilation. METHODS: Pregnant rats grouped as pair-fed control or binge alcohol exposed received a once-daily, orogastric gavage of isocaloric maltose dextrin or alcohol, respectively. On gestational day 20, primary uterine arteries were isolated, cannulated, connected to a pressure transducer, and functional studies were conducted by dual-chamber arteriography. Uterine arteries maintained at constant intramural pressure (90 mm Hg) were maximally constricted with thromboxane, and a dose response for acetylcholine was recorded. RESULTS: The alcohol group exhibited significantly impaired endothelium-dependent, acetylcholine-induced uterine artery relaxation (↓~30%). Subsequently, a dose response was recorded following inhibition of endothelium-derived hyperpolarizing factor (apamin and TRAM-34) and prostacyclin (indomethacin). Acetylcholine-induced relaxation in the pair-fed control decreased by ~46%, and interestingly, relaxation in alcohol group further decreased by an additional ~48%, demonstrating that gestational binge alcohol impairs the nitric oxide system in the primary uterine artery. An endothelium-independent SNP effect was not observed. Immunoblotting indicated that alcohol decreased the level of endothelial excitatory P-Ser(1177)eNOS (P < 0.05) and total eNOS expression (P < 0.05) compared to both the normal and pair-fed controls. P-Ser(1177)eNOS level was also confirmed by immunofluorescence imaging. CONCLUSION: This is the first study to demonstrate maternal binge alcohol consumption during pregnancy disrupts uterine artery vascular function via impairment of the eNOS vasodilatory system.